From Screens to Pages: Contextual Strategies to Boost Gen Z's English Reading Motivation in Rural Indonesian EFL Classrooms - Novri Susanti Suparman; Destri Wahyuningsih; Denny Wahyuni; Roswati Roswati; Ummi Rasyidah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading motivation among Generation Z students in rural Indonesian EFL (English as a Foreign Language) classrooms remains critically low due to digital distractions, outdated materials, and limited home support. While prior studies highlight the benefits of digital engagement and gamification, little is known about how these strategies function in under-resourced, rural settings. This study employed a mixed-methods design using a convergent parallel approach. Quantitative data were collected from 150 senior high school students across SMA, SMK, and MA institutions in Kabupaten Indragiri Hulu, using a questionnaire adapted from the Motivation for Reading Questionnaire (MRQ). Qualitative data were obtained through interviews and focus group discussions with 10 teachers and 10 students. Thematic analysis and descriptive statistics were integrated to identify motivational barriers and context-appropriate strategies. Findings revealed that digital distractions, vocabulary difficulties, lack of family encouragement, and exam-oriented instruction were key factors undermining reading motivation. Only 27% of students reported experiencing interactive or digital reading activities in class. Students expressed preference for digital content but struggled with comprehension due to limited vocabulary and irrelevant materials. Grounded in Self-Determination Theory and Expectancy-Value Theory, the study suggests that increasing students’ autonomy, competence, and task value—through gamified learning, contextualized materials, and family engagement—can significantly boost motivation. These insights offer actionable strategies for teachers and policymakers to revitalize reading culture in rural EFL settings.